1998
DOI: 10.2490/jjrm1963.35.918
|View full text |Cite
|
Sign up to set email alerts
|

Multi-disciplinary Teamwork of Community Care Staff in Service Provisions for the Elderly.

Abstract: Community care professionals were asked to complete a questionnaire concerning individual disabled elderly people living at home for whom they were currently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has been emphasized in Japan that the multi-disciplinary meetings should be held regularly in order to achieve an appropriate care management process (30,39). Matsusaka et al (40) reported that regular meetings brought better results in assessment of clients' needs and in the co-ordination of care services needed for them than could be achieved by a single professional or by meetings between members of only one discipline.…”
Section: Value Of Multi-disciplinary Meetingsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been emphasized in Japan that the multi-disciplinary meetings should be held regularly in order to achieve an appropriate care management process (30,39). Matsusaka et al (40) reported that regular meetings brought better results in assessment of clients' needs and in the co-ordination of care services needed for them than could be achieved by a single professional or by meetings between members of only one discipline.…”
Section: Value Of Multi-disciplinary Meetingsmentioning
confidence: 99%
“…Matsusaka et al (40) reported that such meetings were more effective in obtaining information about the clients to assess their needs, in identifying their health and social care needs and in co-ordinating care services compared with uni-disciplinary meeting or performance by single professionals. The superiority of the multi-disciplinary meetings has led to the adoption of multi-disciplinary meetings as a standard procedure by community rehabilitation agencies in many municipalities.…”
Section: Holding Multi-disciplinary Meetingsmentioning
confidence: 99%
See 3 more Smart Citations